Effectiveness of mathematics teacher performance - Sičiūnienė, Viktorija (Lietuvos matematikos rinkinys, 2016)
This article represents conclusions about an effective mathematics teachers’ work. These conclusions were derived linking teachers questionnaire data to their students test results. Eighth grade student test results were taken from national 2012 and 2014 year student achievement test database. Descriptive statistics, statistical correlation analysis, clustering and generalization methods were used at this research. This article describes an effective working teacher behavior and provides teacher development directions, which in the near future are expected to improve student achievements.